Analisis Penilaian Kinerja Keuangan Dinas Kesehatan Kabupaten Karawang Dengan Menggunakan Metode Value For Money - Permata Sukma, Indah; Muslihat, Asep (AKUNTANSI 45, 2023)
This research was conducted to measure and analyze financial performance in the District Health Office. Karawang in the Health Service Provider Program for UKM and UKP Municipal District Authorities. This research is descriptive research with data collection techniques using observation methods, literature studies and documentation. The method of processing and analyzing data uses the value for money method through Government Agency Performance Reports (LKIP) of the District Health Office. Karawang in 2022. The results of the study show that the financial performance of the District Health Office Karawang is very good and has been oriented to the interests of the community and is guided by 3 indicators of value for money, namely economy, efficiency and effectiveness.